Unveiled optical properties of tetrapyrollic pigments in cryogenic environments - Crépin, C.; Shafizadeh, N.; Chin, W.; Galaup, J.-P.; McCaffrey, J.G.; Arabei, S.M. (Физика низких температур, 2010)
An unexpected phenomenon was revealed in the laser induced fluorescence spectra of free-base (H₂Pc) and zinc (ZnPc) phthalocyanines trapped in rare gas and nitrogen matrices under a moderate increase in the laser intensity. In all matrices the intensity of an emission band near 755 nm increased drastically when pumping the S₁←S₀ transition. This observation was assigned to stimulated emission in a four-level scheme involving a vibronic transition from the lowest electronic state to a vibrational level of the ground state. In the present work, we expose new similar results obtained with porphyrin molecules, i.e. tetra-benzoporphin (TBP). With free-base H₂TBP, stimulated emission was observed in Ar or N₂ matrices, but not in Xe matrices. A possible reason could be a fast inter-system crossing rate due to the heavy atom effect induced by Xe. We also report the observation of persistent burnt spectral holes, although the low efficiency of this process is not competitive with stimulated emission and no decrease of the stimulated emission with time was observed. With ZnTBP, no stimulated emission could be recorded; however the appearance of rather strong phosphorescence was noticed. Similar studies focusing on the stimulated emission phenomenon is that they should allow new insights into site effects and site selectivity.